ANALISA PENGARUH SERVICE QUALITY DAN BRAND IMAGE TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA CAFÉ “COFFEE TOFFEE” DI SURABAYA - Kevin Julian (Jurnal Strategi Pemasaran, 2019)
The phenomenon of coffee in a modern coffee shop becomes a habit of today's society, such as in Surabaya, and other big cities. Modern coffee shops seem to have become middle-class identities for socializing, and many of them also rely on coffee shops as a hangout or meeting place. And also now many coffee shop businesses are competing out there to attract lots of customers, therefore every coffee shop has a strategy to attract many customers. Coffee Toffee is a company engaged in beverage or beverage services in Surabaya. To attract a lot of customers a strategy is needed such as in terms of service quality. Therefore the purpose of this study is the Effect of Service Quality and Brand Image on Customer Satisfaction and Customer Loyalty in Coffee Toffee in Surabaya.               This research was conducted by distributing questionnaires 100 respondents in Surabaya. Analytical technique used is technical quantitative with path analysis method. Keywords: Service Quality, Brand Image, Customer Loyalty , Customer Satisfaction.